Financial Boundary Ambiguity Among Military Spouses. Issue 4 (13th November 2020) - McCoy, Megan; O'Neal, Catherine Walker; Gale, Jerry; Goetz, Joseph; Mancini, Jay A.
Abstract : Objective: The military lifestyle of extended training programs and deployments creates a need to clearly define each partner's roles and responsibilities after each departure and reunion. Background: Previous researchers have discovered that the less ambiguity that occurs when an individual enters or departs the family system, the less likely the family is to experience strain or crisis. One challenging area of boundary definition is finances, as couples tend to avoid talking about money which may contribute to financial boundary ambiguity. Methods: This study applies the contextual model of family stress to examine financial boundary ambiguity and its association with marital quality in the post‐deployment stage. This article presents a theory‐driven exploration of financial boundary ambiguity using the actor–partner interdependence model and structural equation modeling. Results: Study findings indicate that role flexibility, as well as clear and open communication, are related to less financial boundary ambiguity. This, in turn, is related to higher marital quality, although there are differences in the actor and partner effects between financial boundary ambiguity and marital relations. Conclusion: To more fully understand coping and resilience among military couples, the authors applied the contextual model of family stress focused on financial elements to clarify the significance of how the couples navigated their roles and interactions. Implications: Programs focused on financial and relational health should focus on fostering communication around financial roles during periods of transition, such as the deployment cycle. In particular, programs should be oriented around strategies for reducing the stress that surrounds financial uncertainties and strain, in addition to teaching effective financial management.